Smart Fertiliser Recommendations for Maize in Rwanda - Mudereri, B.T.; Chernet, M.; Cyamweshi, A.R.; Kayumba, J.; Nshimiyimana, J.C.; Vandamme, Elke; Uzamushaka, S.; Kreye, C.; Abera, W.; Aubert, C. (2025)
This study evaluated the performance of three fertiliser recommendation strategies: the Blanket Recommendation (BR), Improved Blanket Recommendation (IBR), and Site-Specific Recommendation (SSR), for maize production across Rwanda. Implemented under the RAB–CGIAR partnership (RwaSIS and Sustainable Farming Programme (SFP) initiatives), the trials aimed to determine whether data-driven, site-specific fertiliser management can enhance productivity and profitability compared to the traditional national blanket approach.